PENGARUH PERUBAHAN SOSIAL TERHADAP PEMIKIRAN LITERALISM IBNU HAZM - Yazwardi Yazwardi (An Nisa'a, 2014)
The aggravation of political dissension of Islamic people in early the tenth century and the last eleventh century emptied into the establishment of petty states in Andalusia. Ibnu Hazm considered it as a potential opportunity to begin to convey instructions of law based on ra’yu, which was inherent to the legitimacy of administrator’s policies. Ibnu Hazm’s ra’yu approach has resulted divergence of nash determination used by scholars of law. This article is intended to describe the social background of Ibnu Hazm who finally decided to follow Zhahiri’s way of thinking (literalism), the partern way of thinking which was pioneered by Daud al-Asfahanii. To uncover the various cases of law, which were not in textual context, stated in nash, Ibnu Hazm used al-dalil method. He considered that this method was more benifial. It was not the same as qiyas and it was also free from various influences of ra’yu.        ملخص: لقد آلاندلاع التفرق السياسى للامة إسلامية فى اوائل القرن العاشر وأواحر القرن احد عشر إلى ظهور دويلات فى اندلس, يعتقده ابن حزم كشغرة للافتاء بالرأى  المواقف لقرارات السلطان. فالإعتماد على الرأى قد ابعد علماء السلطان من متطلبات النص. يقصد الكاتب لهذه المقالة أن يبين خلفية اجتماعية لإبن حزم حليث  إختار فى النهاية طريقة التفكير الظاهرى, طريقة التفكير التى بداء بها دأود الآصفهانى فى مقابلة أنواع مسئلة الحكم التى غير مكتوبة نصيا فى النصوصء ابن حزم يستحدم منهاج الدلالة. وهو فى نظره انفع وغير متساويان مع القياس وحر من انواع  تئاثير الرأى.